2004
DOI: 10.1002/jcb.20131
|View full text |Cite
|
Sign up to set email alerts
|

Ime2p and Cdc28p: Co‐pilots driving meiotic development

Abstract: Meiosis can be considered an elaboration of the cell division cycle in the sense that meiosis combines cell-cycle processes with programs specific to meiosis. Each phase of the cell division cycle is driven forward by cell-cycle kinases (Cdk) and coordinated with other phases of the cycle through checkpoint functions. Meiotic differentiation is also controlled by these two types of regulation; however, recent study in the budding yeast S. cerevisiae indicates that progression of meiosis is also controlled by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…The N. crassa genome does not contain an IME1 homolog, but does have one homolog of IME2 (NCU01498) (Borkovich et al 2004). IME2 is a serine-threonine protein kinase that regulates the expression and activity of many early and late meiotic genes; ime2 mutants do not sporulate (Smith and Mitchell 1989;Honigberg 2004). In contrast to S. cerevisiae ime2 mutants, homozygous crosses between N. crassa strains containing a deletion in NCU01498 (ime-2) were fertile and exhibited no sexual cycle defects ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The N. crassa genome does not contain an IME1 homolog, but does have one homolog of IME2 (NCU01498) (Borkovich et al 2004). IME2 is a serine-threonine protein kinase that regulates the expression and activity of many early and late meiotic genes; ime2 mutants do not sporulate (Smith and Mitchell 1989;Honigberg 2004). In contrast to S. cerevisiae ime2 mutants, homozygous crosses between N. crassa strains containing a deletion in NCU01498 (ime-2) were fertile and exhibited no sexual cycle defects ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The meiotic division is a differentiation program precisely controlled by the action of protein kinases (34). Regulatory circuits check the occurrence of the specific meiotic division (meiose I) that should be coordinated with DNA replication and recombination to produce the correct segregation of homologous chromosomes into the gametes (35).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have shown that Ime2 regulates multiple steps in meiotic development, including pre-meiotic S-phase and entry into the meiotic divisions, as well as the transcriptional program of meiosis at the early and middle phases (10). In addition, it has been suggested that Ime2 can regulate exit from MI (23).…”
Section: Discussionmentioning
confidence: 99%